Lectotypification, emended description and distribution of Planothidium distinctum (Achnanthidiaceae, Bacillariophyceae) - Buczkó, Krisztina; Wojtal, Agata Z.; Magyari, Enikő K. (Phytotaxa, 2013)
The rare boreo-alpine, oligotraphenic diatom Planothidium distinctum (= Achnanthes distincta) was first described from the western Alps in 1954. Achnanthes hirta, a species described in 1970 from the Pyrenees, is regarded as a heterotypic synonym of Planothidium distinctum but almost all morphological details of P. distinctum are known from the type material of Achnanthes hirta. On the basis of reinvestigation of original samples typification and emended description of P. distinctum were carried out by means of LM and SEM. This study extends the distribution of P. distinctum to the Carpathians where occasional valves were found in the lateglacial (ca 15,000–14,000 cal yr BP) lacustrine sediment of a mountain lake (Retezat Mts, Southern Carpathians, Romania).